From Landing site to Local Centre - Jette Linaa (Danish Journal of Archaeology)
The Viking Age represents a period of significant dynamism, during which local centres and urban sites participated to varying extents in maritime networks. This paper investigates the development, activities, and maritime engagement of the Danish town of Aarhus, located on the East Coast of Jutland, during the Viking Age. In previous research, Aarhus has been portrayed as a prominent town founded in the 8th century with substantial ties to maritime networks. However, this study challenges that narrative through a comparative analysis of structures and 16,000 from 20 excavations—contextualised alongside findings from Ribe, Hedeby, and Kaupang. The analysis indicates that 8th- and 9th-century Aarhus was primarily an agrarian settlement focused on exploiting coastal resources and exhibiting weak maritime connections. Despite the site's fortification in the early 10th century, the town's activities remained unchanged. It was not until the late 10th century that Aarhus began to develop characteristics of a town, marked by local trade, denser settlement and specialised crafts, yet significant maritime contacts were still absent. Consequently, Aarhus did not emerge as a key hub in Viking Age maritime networks, and its strategic geographic position between the Baltic and the North Sea remained unrealised until the Middle Ages.